Targeted inhibition of Gus-expressing Enterococcus faecalis to promote intestinal stem cell and epithelial renovation contributes to the relief of irinotecan chemotoxicity by dehydrodiisoeugenol - Ruiyang Gao; Bei Yue; Cheng Lv; Xiaolong Geng; Zhilun Yu; Hao Wang; Beibei Zhang; Fangbin Ai; Ziyi Wang; Donghui Liu; Zhengtao Wang; Kaixian Chen; et al. (Acta Pharmaceutica Sinica B)
Irinotecan (CPT11) chemotherapy-induced diarrhea affects a substantial cancer population due to β-glucuronidase (Gus) converting 10-O-glucuronyl-7-ethyl-10-hydroxycamptothecin (SN38G) to toxic 7-ethyl-10-hydroxycamptothecin (SN38). Existing interventions primarily address inflammation and Gus enzyme inhibition, neglecting epithelial repair and Gus-expressing bacteria. Herein, we discovered that dehydrodiisoeugenol (DDIE), isolated from nutmeg, alleviates CPT11-induced intestinal mucositis alongside a synergistic antitumor effect with CPT11 by improving weight loss, colon shortening, epithelial barrier dysfunction, goblet cells and intestinal stem cells (ISCs) loss, and wound-healing. The anti-mucositis effect of DDIE is gut microbiota-dependent. Analysis of microbiome profiling data from clinical patients and CPT11-induced mucositis mice reveals a strong correlation between CPT11 chemotoxicity and Gus-expressing bacteria, particularly Enterococcus faecalis (E. faecalis). DDIE counters CPT11-induced augmentation of E. faecalis, leading to decreased intestinal Gus and SN38 levels. The Partial Least Squares Path Model (PLS-PM) algorithm initially links E. faecalis to dysregulated epithelial renovation. This is further validated in a 3D intestinal organoid model, in which both SN38 and E. faecalis hinder the formation and differentiation of organoids. Interestingly, colonization of E. faecalis exacerbates CPT11-induced mucositis and disturbs epithelial differentiation. Our study unveils a microbiota-driven, epithelial reconstruction-mediated action of DDIE against mucositis, proposing the ‘Gus bacteria–host–irinotecan axis’ as a promising target for mitigating CPT11 chemotoxicity.